Understanding local perceptions of impacts of climate change among small-scale Sama-Bajau fishers and their patrons in Wakatobi National Park, Indonesia - Abu Samah, Asnarulkhadi; Maruf, Amar; Ahmad, Nobaya; Hamsan, Hanina (Shima Publishing, 2024)
Understanding similarities and differences in perceptions of climate change impacts aids in the development of co-adaptation strategies. While there has been extensive research on perceptions of climate change impacts among small-scale fishing communities, studies focusing on the perspectives of maritime tribes, fishers, and their respective patrons in small islands are notably scarce. The current study compares the perceptions of climate change impacts by Sama-Bajau fishers and their patrons in Wangi-Wangi Island of Wakatobi National Park. Data was collected through in-depth interviews, casual conversations, field observation, and secondary data analysis between August 2021 and February 2022. Findings revealed that although fishers and their patrons similarly perceived some impacts, they perceived others differently because of distinct sources of information and experience. Fishers, middlemen and employees of fishing companies perceived the impacts through personal observation and information from other fishers while government and nongovernmental officers relied on scientific reports and personal experience in addition to the information given by the fishers. Future research should explore context-specific coping, adaptation and transformation measures based on local perceptions and diverse patronclient relationships to inform policy development.